PENGARUH PEMBERIAN INFUSUM DAUN SALAM (Eugenia polyantha W) PADA EKSKRESI ASAM URAT TIKUS WISTAR JANTAN - Dharmayanti, Agustin Wulan Suci; Apriono, Dwi Kartika (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2012)
High degree of uric acid into blood or called hyperurecemia, could be caused by increasing of uric acid production, but excretion of uric acid that passed through renal decreased. Effort for overcoming, it was used drug that have diuretic effect. Bay leave was one of plant that can be used as diuretic. This study aimed to know ability bay leave (Eugenia polyantha W) to increase excretion of uric acid at male rats. This study was experimental laboratory study with pre and post control group design and used 30 sample male rats. The samples were divided into 6 groups. Before treatment urine of samples were taken in tubes for 24 hours. Then, samples were treated with high purin feeding and given bay leaves extract twice a day for 5 days. At 6th day, urine of samples were collected and centrifuged for getting urine sediment. They were observed and counted amount of uric acid sediment that use microscope. Result of anova test showed there are differences significantly amount of uric acid sediment for 24 hours at male rat urines, after they are given bay leaves extract in many dozes, aquadest sterile, and probenesid (p < 0,005). Bay leaves have ability to increase amount of uric acid excreation. Flavonoid that be contented in bay leaves can increase catch point in renal for producting urine and decrease reabsorbsion of uric acid through proximale kontortus tubule of renal, so excretion uric acid sediment increase. Flavonoid also had antioxidane effect that can inhibit xantine oxidase enzyme and reaction of superoxide, so formation uric acis is lower or inhibit. Conclution this study is infusa of bay leaves 100 % in many dozes cab increase excretion of uric acid sediment at male rats.